Temporal changes in headwater streams macroinvertebrate assemblages during the snowmelt season in northeast china - Gao, Yufu; Rong, Liping; Cao, Lina; Li, Kun; Lin, Chenlu; Zhang, Zhenxing; Xiang, Hongyong; Yang, Haijun (Frontiers in Environmental Science, 2022)
Mid-latitude areas such as Northeast China is predicted to have warmer temperature according to IPCC 6th which may influence the duration and magnitude of snowmelt season. What remains unknown, however, is how annual snowmelt can influence biodiversity of macroinvertebrate communities, especially in headwater streams in Northeast China. Here, investigated the temporal changes (before, during, and after the snowmelt period) of macroinvertebrate communities and stream physicochemical characteristics in five headwater streams in Northeast China. We found that: (1) Macroinvertebrate taxa richness, density, Shannon diversity, and functional diversity were lower in the melting period than in the other two periods, while biomass and dominant species were significantly higher in this period; (2) As to functional traits, macroinvertebrates taxa has "erosional", "strong swimming ability", "some attachment", "streamlined shape" and "large size at maturity" traits in the melting period was significantly higher than in the other two periods; and (3) Redundancy analysis (RDA) and multiple linear regression model found that temperature, turbidity and velocity were key environmental factors affecting the functional traits of macroinvertebrates during the whole snowmelt process. This study could provide crucial data to support biodiversity conservation and ecosystem restoration of freshwater ecosystems in mid-to high-latitude and alpine areas.